Fine as a type of disciplinary penalty against prisoners of war - Yu. V. Orel (Bulletin of Kharkiv National University of Internal Affairs)
The article examines national legislation and international legal acts operating in the field of international humanitarian law, in particular, regarding the treatment of prisoners of war. It has been emphasized that in the modern legal science of Ukraine there are no relevant scientific works devoted to the study of issues of bringing prisoners of war to disciplinary responsibility.